Effects of fatigue on patellar tendon loading during the landing phases of a stop-jump movement - Edwards, S.; Munro, B.; Cook, J.; Purdam, C.; Steele, J. R. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Therefore, the purpose of this study was to establish whether there were any significant differences in the patellar tendon forces generated by athletes during the landing phases of a stop-jump (SJ) movement before and after fatigue induced by repetitive SSC exercises. Eighteen soccer and basketball players performed a SJ movement before and after a fatigue protocol. During each SJ trial, three-dimensional kinematic, kinetic and electromyographic data for each subject`s lower limbs were recorded. When fatigued, athletes significantly (p < 0.05) reduced their patellar tendon forces during the SJ movement by reducing knee and hip flexion. Whether "stiff limb" landings reduces the risk of developing patellar tendinopathy by decreasing patellar tendon loading during jumping requires further investigation.